Androgen‐responsive tripartite motif 36 enhances tumor‐suppressive effect by regulating apoptosis‐related pathway in prostate cancer. Issue 12 (30th October 2018) - Kimura, Naoki; Yamada, Yuta; Takayama, Ken‐ichi; Fujimura, Tetsuya; Takahashi, Satoru; Kume, Haruki; Inoue, Satoshi
Abstract : Tripartite motif 36 (TRIM36) belongs to the TRIM family, most members of which are involved in ubiquitination and degradation of target proteins by functioning as E3 ubiquitin ligases. The function of TRIM36 has not been well documented, therefore, we investigated the clinical significance and function of TRIM36 in human prostate cancer (PC). Multivariate logistic regression analysis showed that TRIM36 immunoreactivity was an independent predictor of cancer‐specific survival of PC patients. Gain‐of‐function study revealed that overexpression of TRIM36 suppressed cell proliferation and migration of LNCaP, 22Rv1, and DU145 cells. Moreover, TRIM36 knockdown using siRNA suppressed apoptosis and promoted cell proliferation and migration in LNCaP and 22Rv1 cells. Furthermore, our microarray analysis revealed that the apoptosis‐related pathway was significantly upregulated by TRIM36 overexpression. The TUNEL assay showed that apoptosis promoted by docetaxel treatment was alleviated in siTRIM36‐treated LNCaP and 22Rv1 cells. Taken together, these results suggest that high expression of TRIM36 is associated with favorable prognosis and that TRIM36 plays a tumor‐suppressive role by inhibiting cell proliferation and migration as well as promoting apoptosis in PC. Abstract : Tripartite motif 36 has tumor‐suppressive effects in prostate cancer. The effect was caused by regulation of apoptosis‐related genes.